Influenza A and B viruses expressing altered NS1 proteins: A vaccine approach - Talon, Julie (The National Academy of Sciences, 2000)
We propose a rational approach to the generation of live viral vaccines: alteration of virally encoded type I IFN antagonists to attenuate virulence while retaining immunogenicity. We have explored this concept by using the influenza virus. Previously we have shown that the NS1 protein of influenza A virus possesses anti-IFN activity. We now present evidence that influenza A and B viruses encoding altered viral NS1 proteins are highly attenuated in the mouse host, yet provide protection from challenge with wild-type viruses.